Curcumin-Loaded Chitosan/Gelatin Composite Sponge for Wound Healing Application - Van Cuong Nguyen; Van Boi Nguyen; Ming-Fa Hsieh (International Journal of Polymer Science)
Three composite sponges were made with 10% of curcumin and by using polymers, namely, chitosan and gelatin with various ratios. The chemical structure and morphology were evaluated by FTIR and SEM. These sponges were evaluated for water absorption capacity, antibacterial activity, in vitro drug release, and in vivo wound healing studies by excision wound model using rabbits. The in vivo study presented a greater wound closure in wounds treated with curcumin-composite sponge than those with composite sponge without curcumin and untreated group. These obtained results showed that combination of curcumin, chitosan and gelatin could improve the wound healing activity in comparison to chitosan, and gelatin without curcumin.